Design and Molecular Docking Studies of Quinazoline Derivatives as Antiproliferation - Anita Puspa Widiyana; Galih Satrio Putra; Luthfi Ahmad Muchlashi; Mellany Ika Sulistyowaty; Tutuk Budiati (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2016)
Background: Nowadays, a lot of new active substances as anticancer agents have been developed. One of the protein targets of anticancer is selective cyclooxygenase-2 (COX-2). Selective COX-2 is the regulator of cell proliferation. Objective: In this research, quinazoline derivatives were used to design the anticancer agent through a selective COX-2 inhibition. The potential activity of quinazoline derivatives could be increased by substitution in position 2 and 3 of quinazolinone. Molecular docking of selective COX-2 inhibition was required to predict their antiproliferation activity. Methods: The molecular docking of quinazoline derivatives was carried out using Molegro Virtual Docker (MVD) Ver.5.5. Twenty-one of quinazoline derivatives were docked into selective COX-2 with PDB code 3LN1. The interaction was evaluated based on the re-ranked score comparison between quinazoline derivatives with co-crystallized ligand CEL_682. Celecoxib was used as the reference to this research. Results: The result indicated that 18 of 21 quinazoline derivatives showed the approximately re-ranked score -131.508 to -108.418 kcal/mol. Eight of these 18 new quinazoline derivatives have re-ranked score better than Celecoxib. Conclusions: In conclusion, 8 of the new quinazoline derivatives are feasible to be synthesize and performed their in vitro evaluation.